Palm Derived Products: A Bibliometric Analysis of Industrial Downstreaming - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of global research on palm-derived products with a focus on industrial downstreaming. Using data extracted from the Scopus database and visualized through VOSviewer, the analysis maps the intellectual structure, thematic evolution, and collaborative patterns within the domain. Results reveal that